2023
DOI: 10.3390/healthcare11040587
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Hybrid Closed-Loop System for Glycemic Control in Two Pediatric Patients with Type 1 Diabetes Undergoing Minor Surgery

Abstract: Technological progress in the treatment of type 1 diabetes requires doctors to use modern methods of insulin therapy in all areas of medicine that patients may come into contact with, including surgical interventions. The current guidelines indicate the possibility of using continuous subcutaneous insulin infusion in minor surgical procedures, but there are few reported cases of using a hybrid closed-loop system in perioperative insulin therapy. This case presentation focuses on two children with type 1 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…To our knowledge, this is the largest case series of hybrid closed loop system use in the perioperative period in pediatric patients, and the first to discuss some of the newer hybrid closed loop systems. 16 While BG management was appropriate during these cases, we found that patients who initiated exercise activity mode on t:slim Control-IQ the night before surgery arrived to the preoperative area with higher BG. Based on this experience, we recommend initiating exercise activity mode (t:slim) or activity feature (Omnipod 5) upon arrival to the preoperative area before the procedure, allowing a shorter period of time at a higher target BG.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…To our knowledge, this is the largest case series of hybrid closed loop system use in the perioperative period in pediatric patients, and the first to discuss some of the newer hybrid closed loop systems. 16 While BG management was appropriate during these cases, we found that patients who initiated exercise activity mode on t:slim Control-IQ the night before surgery arrived to the preoperative area with higher BG. Based on this experience, we recommend initiating exercise activity mode (t:slim) or activity feature (Omnipod 5) upon arrival to the preoperative area before the procedure, allowing a shorter period of time at a higher target BG.…”
Section: Discussionmentioning
confidence: 83%
“…To our knowledge, this is the largest case series of hybrid closed loop system use in the perioperative period in pediatric patients, and the first to discuss some of the newer hybrid closed loop systems 16 . While BG management was appropriate during these cases, we found that patients who initiated exercise activity mode on t:slim Control‐IQ the night before surgery arrived to the preoperative area with higher BG.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…During the periprocedural periods, glucose levels remained within the target range. AHCL reports on the day of the surgical procedure were very similar to those 2 weeks prior to hospital admissions and revealed CGM metrics within the recommended clinical targets [ 45 ]. A case study of an 11-year-old subject with T1D from Saudi Arabia reported that AHCL provided satisfactory glucose control during fasting for more than 14 h per day, which is typical during the month of Ramadan.…”
Section: Summary Of Case Reportsmentioning
confidence: 99%